The effect of reading performance on high school science achievement - Ireland, Julie D. (Curtin University, 1987)
This study was undertaken to investigate the relationship between student reading performance and achievement in science. Many students have difficulties comprehending written materials presented to them in science and many tests used to measure achievement in science rely heavily on reading ability. Students may have trouble demonstrating their science knowledge due to their lack of reading skills.In this study, the reading ages and science achievement scores of students were calculated. Twenty activity cards used to teach the science topic Plants and Animals were modified to reduce the language difficulty level. All students in two Year 8 science classes used the modified activity cards and modified science achievement measures. Five students were selected to form a sub-sample of the class group for in-depth observations, interviews, and analysis. These students were low performance readers who achieved poorly on science topic tests even though they had excellent work habits. The student reading ages in the class groups ranged from 8 years 1 month to above 16 years 10 months.The reading performance data were found to correlate significantly with science achievement as measured on topic tests. Class 1 produced a correlation coefficient of 0.46, while Class 2 produced a correlation coefficient of 0.75. In this study it appears that science achievement is related to reading performance.Qualitative analysis of data from the five students in the sub-sample showed that the modified activity cards were relatively easy to use. Students could work on the cards independently. This study demonstrated that textual material needs to be presented at an appropriate reading level for independent learning to occur.All of the students in the sub-sample demonstrated improved science achievement on the modified Plants and Animals topic test. In addition, most other students in the study improved their performance on the modified science test. Thus, the modiifications appeared to make it easier for most students to demonstrate their science achievement.A positive correlation was found between student reading age and science achievement. Reading performance may be a critical factor in achievement on science tests. If this is the case, learning strategies must be developed that focus on helping students to utilize textual materials effectively.